They observe an image and we, through visual anthropology, observe a Geometry in the skeleton of the wattle and daub house - Quimuanga, Zeca Catuco André; Almouloud, Saddo Ag (Educação Matemática Debate, 2024)
Going to the field, so that this immersion allows contact with others, characterizes the production of data in classical anthropological practice. In an Anthropology in which natives express themselves through images, the possibility of using it as a field and research instrument opens up, instead of just being observation records. In the discussion present in this essay, we sought to identify, based on observational immersion, in a visual anthropological perspective, the geometric concepts present in the skeleton of a wattle and daub house and their connections with teaching. The results showed that the skeleton is supported by rectangles, squares, trapezoids and triangles, resulting from the intersections between horizontal, vertical and oblique sticks and/or wood.